(untitled) (Revista Innova Educación, 2021)
The objective was to review various scientific articles to identify the relevant concepts, characteristics, and theories that underpin the construction of creative thinking and analyze the proposals that contribute to its improvement. For this, databases such as Ebsco, Scopus, Eric were reviewed, from which 50 relevant articles were selected. The methodology used is descriptive-analytical, which allowed us to reach the following results: there are a diversity of definitions, characteristics, and strategies that promote the improvement of creative thinking, and its development in students is crucial for good growth in society. In conclusion, the educational system must promote the knowledge and development of creative thinking in the teaching-learning process since this skill is required to access a job.